2017
DOI: 10.1039/c7cc00676d
|View full text |Cite
|
Sign up to set email alerts
|

Designing an anion-functionalized fluorescent ionic liquid as an efficient and reversible turn-off sensor for detecting SO2

Abstract: A novel anion-functionalized fluorescent ionic liquid was designed and prepared, which was capable of capturing sulphur dioxide with high capacity and could also be used as a good colorimetric and fluorescent SO sensor. Compared to conventional fluorescent sensors, this fluorescent ionic liquid did not undergo aggregation-caused quenching or aggregation-induced emission, and the fluorescence was quenched when exposed to SO, and the fluorescence would quench when exposed to SO. The experimental absorption, spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 29 publications
0
25
0
Order By: Relevance
“…11 Ionic liquids are desirable inclusions for gas sensing applications due to their good gas solubility, tunable physiochemical properties, and air and water stability. 12,13 The disparity in the surface energy and hydrophobicity of conjugated polymers and liquid state ionic liquids can cause difficulties in realising efficient devices; instead, they often have slow turn-on and require prebiasing. 14 Recently, the development of a solid-state ionic liquid (SSIL) with matching surface energy and stable ion diffusion has been shown to significantly improve device performance.…”
Section: Introductionmentioning
confidence: 99%
“…11 Ionic liquids are desirable inclusions for gas sensing applications due to their good gas solubility, tunable physiochemical properties, and air and water stability. 12,13 The disparity in the surface energy and hydrophobicity of conjugated polymers and liquid state ionic liquids can cause difficulties in realising efficient devices; instead, they often have slow turn-on and require prebiasing. 14 Recently, the development of a solid-state ionic liquid (SSIL) with matching surface energy and stable ion diffusion has been shown to significantly improve device performance.…”
Section: Introductionmentioning
confidence: 99%
“…The Gaussian 09 package 33 was chosen to conduct all the calculations. Geometry optimizations were carried out unrestrained at the model chemistry of B3LYP 34 /6–311 ++ G(d, p) 35 (SDD 36 for the third to fifth period elements), which has shown appreciable performance over a wide range of NHCs 5 , 7 , 8 , 10 , 12 , 24 , 28 . Frequency analyses with the same model chemistry followed the structure optimization to identify energy minimum.…”
Section: Methodsmentioning
confidence: 99%
“…Actually, SO 2 rarely breaks the ion pair 8 , 15 , 23 – 27 . Still for simplicity, calculations of SO 2 interacting with ILs were routinely carried out in the absence of cation since the cation effects are assumed to be negligible 5 , 7 , 9 , 10 , 12 , 28 . To date, whether cation promotes or restrains the binding between NHC and SO 2 has not yet been clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical analysis further showed that IL-based array can be promising through providing unique response patterns for each vapor [ 105 ]. In addition, further modification of ILs and incorporation with other materials (e.g., ethyl cellulose matrix, electrospun nanofiber, or carbon nanotubes) have led to successful sensing of CO 2 and SO 2 [ 106 , 107 , 108 , 109 ].…”
Section: Ionic Liquids and Its Use For Adsorption Analysis Of Gasementioning
confidence: 99%